The Influence of Career Development and Job Satisfaction on Teacher Performance at SMA Negeri 1 Sungai Raya, Kubu Raya Regency, West Kalimantan - Asrin Asrin; Siti Patimah (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2023)
Human resource management is the science of managing all human resources in an educational institution. One of the human resources that has a very dominant role in an educational institution is the teacher. Teachers are the spearhead of the success or failure of an educational institution. Without teachers it is impossible for an educational institution to be able to stand well. This is because functionally teachers are people who carry out activities and provide knowledge, skills, education and experience to students. Teacher performance is generally the result of work achieved in carrying out their duties. Likewise with teacher performance at SMA Negeri 1 Sungai Raya. The aims of this research is to determine the influence of career development on teacher performance at SMA Negeri 1 Sungai Raya, Kubu Raya Regency, West Kalimantan, both partially and simultaneously. The sample used in this study was 59 respondents, with data collection tools using a questionnaire. The data analysis methods used are classical assumption tests and multiple linear regression analysis with coefficient of determination hypothesis tests, partial tests and simultaneous tests. The results of this research are 1) Career Development variables influence Teacher Performance; 2) The Job Satisfaction variable influences Teacher Performance, and; 3) Simultaneously, Career Development and Job Satisfaction influence Teacher Performance by 53.5%.